Against academic "resourcification": collaboration as delinking from extractivist "area studies" paradigms - Donovan, Victoria (Canadian Slavonic papers, 2023)
This article engages Asia Bazdyrieva's idea of the "resourcification" of Ukraine - that is, the reduction of Ukraine in Soviet and Western geopolitical imaginations to a mere extraction resource - to develop and criticize the idea of "academic resourcification." The author argues that Western researchers have often treated Ukrainian (and other non-Western) subjects as extraction resources, mining their expertise and knowledge, without acknowledging their agency or contributions in their work. The article argues for the decolonization of Western academic practice in the form of "delinking" from such exploitative and extractivist paradigms of knowledge production and instead aspiring, in the words of the decolonial scholar Walter Mignolo, to "thinking and doing otherwise." Asking what it means to decolonize academia, the article turns for inspiration to Ukrainian decolonial researcher-artist-activists, considering the ways in which these individuals are modelling more equitable and ethical forms of knowledge production. The article ends by advocating collaborative methods - that is, the co-production of knowledge with local thinkers, rather than about them - as a productive model for Western scholars in their efforts to decolonize their research.